Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) yang di Pupuk Dengan Pupuk Organik Cair Pada Media Tanam Hidroponik - I Gede Agus Mahendra; I Gusti Ngurah Alit Wiswasta; Putu Eka Pasmidi Ariati (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
Mustard is a horticultural product that is consumed by almost all levels of society everywhere including in Indonesia. Mustard or Caisim (Brassica juncea L.) belongs to the family of Brassicaceae, the leaves are long, smooth, hairless, and not cropped. Hydroponically cultivated plants grow twice as fast as conventional systems. This is due to direct contact between roots and oxygen, optimum acidity, and an increase in the balancing absorption of nutrients and nutrition. D.I.GROW Organic Fertilizer is Liquid Organic Fertilizer made from Ascophyllum nodosum, a type of Chocolate Seaweed taken from the North Atlantic Sea. Naturally, Ascophyllum nodosum, which contains abundant nutrition, such as: Macro Minerals, Micro Minerals, Amino Acids, Humic Acid, Gibberellins, Auxin, Cytokinins and various Nutrition elements needed by all types of Plants and Animals. It used during the Vegetative period. Stimulate and increase the growth of roots, stems, leaves and buds / tillers quickly with the correct dose used for vegetable leaves 3-5 ml / liter of water. The advantages of a hydroponic system are the using of lands does not need to be too extensive, plants are cultivated do not need soil, there is no risk of continuous planting throughout the year, the quantity and quality of production is higher and cleaner, used of fertilizer and the water more efficient, the plants period are shorter, used of pests and diseases more easily and environmentally friendly. Based on the results of the study it can be concluded that the concentration of liquid fertilizer suitable for using in mustard plants in hydroponic media is 3 mL / liter because it has the highest fresh weight above the base of the plant which is 37.78 grams which indicates maximum plant growth. This can be seen from giving of D.I.GROW 3 ml / L fertilizer has the highest plant height, number of leaves, fresh weight above and below of the base of the plant. The nutrients given to plants must be in the right composition. If deficiency or excess, it will be disturbed plant growth and the results obtained are less than optimal. Hydroponic nutrient solutions contain all micro and macro nutrients in appropriate amounts, hydroponic fertilizers are also more stable and dissolve quickly in water because they are in a purer form